Factors affecting the hydrolysis of the antibiotic amoxicillin in the aquatic environment. (January 2023) - Ecke, Alexander; Westphalen, Tanja; Retzmann, Anika; Schneider, Rudolf J.
Abstract: The environmental fate of the frequently used broad-spectrum β-lactam antibiotic amoxicillin (AMX) is of high concern regarding the potential evolution of antimicrobial resistance (AMR). Moreover, it is known that AMX is prone to hydrolysis, yielding a variety of hydrolysis products (HPs) with yet unknown effects. Studies to identify those HPs and investigate their formation mechanisms have been reported but a long-term study on their stability in real water samples was missing. In this regard, we investigated the hydrolysis of AMX at two concentration levels in four distinct water types under three different storage conditions over two months. Concentrations of AMX and four relevant HPs were monitored by an LC-MS/MS method revealing pronounced differences in the hydrolysis rate of AMX in tap water and mineral water on the one hand (fast) and surface water on the other (slow). In this context, the occurrence, relative intensities, and stability of certain HPs are more dependent on the water type than on the storage condition. As clarified by ICP-MS, the main difference between the water types was the content of the metals copper and zinc which are supposed to catalyze AMX hydrolysis demonstrating an effective method to degrade AMX at ambient conditions. Graphical abstract: Image 1 Highlights: Hydrolysis kinetics and pathways of amoxicillin vary strongly in different water types. These differences could be ascribed to the content of heavy metal ions (precisely: Cu and Zn) in the water samples. The time-resolved formation and long-term stability of selected hydrolysis products were monitored. A new degradation pathway to yield a considerably stable end product of amoxicillin hydrolysis is proposed. These results have relevance to water treatment, environmental contamination and drinking water safety.